Mapa bagien Polesia Daniela Zwickera z 1650 roku – dwa znane i dwa nieznane jej egzemplarze odkryte w zbiorach polskich - Kozica, K. (Історико-географічні дослідження в Україні, 2019)
W artykule przedstawiono najnowszy stan badań nad jedną z najrzadszych map
w historii kartografii polskiej – mapą bagien Polesia Daniela Zwickera (1612–1678) z
1650 r. Wyrytowana i opublikowana w Gdańsku przez Wilhelma Hondiusa (po 1597–
1652) uważana jest przez K. Buczka (1963) za jego najlepsze bądź jedno z najlepszych
dzieł. Jeszcze do niedawna uważana była za nieobecną w polskich zbiorach publicznych,
a cała dotychczasowa literatura przedmiotu wymieniała tylko dwa jej znane zachowane
egzemplarze w zbiorach zagranicznych: w Dreźnie i w Wiedniu. Ostatnie badania
autora pozwoliły na odkrycie jej trzeciego egzemplarza w zbiorach polskich – w Bibliotece
Raczyńskich w Poznaniu. Czwarty egzemplarz tej mapy autor odkrył w zbiorach
Muzeum Warszawy. Mało tego ten odkryty czwarty egzemplarz mapy bagien Polesia jest
jej drugim stanem z tego samego roku czyli z 1650 r. (dodana m.in. informacja o bitwie
łojowskiej), którego istnienie przewidywał K. Buczek (1963) na podstawie przerysu tej
mapy zamieszczonego w tłumaczeniu St.B. Gorskiego dzieła o czerwcu polskim J. Hamela
(Wilno 1837). Ponadto prawdopodobnie piąty egzemplarz mapy Zwickera znajduje się w obiegu antykwarycznym. The map of the Polesie marshes from 1650 by the outstanding Socinian and physician
from Gdańsk, Daniel Zwicker (1612-1678), is one of the rarest and most precious
maps in the history of Polish cartography. It is also famous for showing on a map for
the first time the places where a scale insect (Porphyrophora polonica) occurs. In the
middle ages larvas of this insect were used to produce a valuable raw material to obtain
red pigment called carmine dye. The map was engraved and published in Gdańsk by
the well-known engraver Wilhelm Hondius (after 1597-1652). According to K. Buczek
(The history of Polish cartography from the 15th to the 18th century, Amsterdam 1982)
the map is of little significance from a cartographic point of view, but has considerable
artistic value and was probably the best map produced by W. Hondius. Until recently no
copy of this map was known to exist in Polish public cartographical records/collections,
and until now all published map references in Polish or other languages quoted only two
known copies of the map preserved in foreign collections: in Dresden (Sächsische Landesbibliothek
- Staats- und Universitätsbibliothek, sign.: H. Polon. 23, III) and in Vienna
(Österreichische Nationalbibliothek, sign.: 389.030-F.K. 23, Taf. 42). The author’s latest
research brought to light a third copy in 2011, this time in a Polish public collection - the
Raczynski Library (Biblioteka Raczyńskich) in Poznań (sign.: M II 971 / 5706), which was
purchased in 1985 after the death of a private collector. A fourth copy of this map was
discovered by the author in the Warsaw Museum (Muzeum Warszawy) in a composite
atlas by Matthäus Seutter (1678-1757) purchased in 1960. What is more, this fourth copy
of the map of the marshes of Polesie is the second state of the Zwicker map from the
same year - 1650 (showing, among other additional details, information about the battle
of Łojowogród on 31 July 1649). The existence of a second state was already presumed
by K. Buczek (1963) on the basis of a copy of that state published in a Polish translation
by Stanisław Batys Gorski of a work on the said insect (Porphyrophora polonica) by
J. Hamel (Wilno 1837). A fifth copy of the Zwicker map is reputed to exist in the trade.